The stained glass of Herkenrode Abbey - Lecocq, Isabelle (Corpus vitrearum Medii Aevi - Great Britain, 2021)
The surviving glazing from Herkenrode Abbey in modern-day Belgium constitutes the most significant body of Flemish stained glass in the world. Much of it was executed, in the 1530s, for the abbey church, and some of the rest was made for the abbess's private chapel. An Englishman, Sir Brooke Boothby, took advantage of the secularization of the monasteries to purchase the abbey churhc glazing, in 1802, and it now adorns windows in Lichfield Cathedral and the church of St Mary (Shrewsbury); the glazing from the abbess's private chapel came to England via a different route and now stands over the main altar in the church of St Giles (Ashtead). Recent conservation has afforded the opportunity to study the glass in Lichfield Cathedral in depth, and the ensemle is presented here fully for the first time. A general historical introduction on Herkenrode Abbey prefaces sections on the three locations in England where the glass is now found. The account draws on extensive research into artistic practice in the Low Countries to outline the glazing's art-historical context, and on the rich documentation in the Lichfield Cathedral archives to trace a detailed history of the glazing's reception in England